EB1 surges promote ciliary outer-segment growth through periodic tubulin influxes into the Drosophila olfactory cilia. - Agarwal, R.G.; Iyer, S.S.; Barbora, A.; Desai, M.; Gadgil, Y.; Jana, S.C.; Ray, K. (Journal of Cell Science, 2026)
Sensory cilia have a complex bipartite architecture containing 9+0 connecting cilia at the inner segment and singlet microtubule-supported highly membranous outer segments essential for receptor display. The mechanisms underlying the formation of such highly branched morphology and its microtubule-rich ciliary cytoskeleton are unclear. Here, we show that individual olfactory cilium inside the large basiconic sensillum grows in episodic steps following several pulsatile influxes of tubulin in developing Drosophila antenna. Transient elevations of the microtubule end-binding protein EB1 precede the tubulin influx events. We also demonstrate that EB1 interacts explicitly with the cargo-binding tail domain of Drosophila KLP68D, a kinesin-2? orthologue. Loss of EB1 in olfactory neurons during the outer segment growth reduces the tubulin influx and affects cilia stability. Finally, we show that the EB1 and tubulin influxes into the distal outer segment of the olfactory cilia require kinesin-2. Altogether, our findings elucidate a role of active EB1 transport in promoting the growth and stability of long-lived metazoan cilia involved in sensory perception.